Lipogenic effects of androgen signaling in normal and malignant prostate - Chui Yan Mah; Zeyad D. Nassar; Johannes V. Swinnen; Lisa M. Butler (Asian Journal of Urology)
Prostate cancer is an androgen-dependent cancer with unique metabolic features compared to many other solid tumors, and typically does not exhibit the “Warburg effect”. During malignant transformation, an early metabolic switch diverts the dependence of normal prostate cells on aerobic glycolysis for the synthesis of and secretion of citrate towards a more energetically favorable metabolic phenotype, whereby citrate is actively oxidised for energy and biosynthetic processes (i.e. de novo lipogenesis). It is now clear that lipid metabolism is one of the key androgen-regulated processes in prostate cells and alterations in lipid metabolism are a hallmark of prostate cancer, whereby increased de novo lipogenesis accompanied by overexpression of lipid metabolic genes are characteristic of primary and advanced disease. Despite recent advances in our understanding of altered lipid metabolism in prostate tumorigenesis and cancer progression, the intermediary metabolism of the normal prostate and its relationship to androgen signaling remains poorly understood. In this review, we discuss the fundamental metabolic relationships that are distinctive in normal versus malignant prostate tissues, and the role of androgens in the regulation of lipid metabolism at different stages of prostate tumorigenesis.